STUDI KOMPARASI KINERJA KEUANGAN PERBANKAN ANTARA BANK SYARIAH DAN BANK KONVENSIONAL - Nurjanah, Anna (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
The purpose of this study was to analyzed financial performance. Bank Rakyat Indonesia Syariah with PT. Bank Rakyat Indonesia Tbk seen from CAR, NPL, ROA, ROA, and LDR. Analyze comparative financial performance. Bank Rakyat Indonesia Syariah with PT. Bank Rakyat Indonesia Tbk during the period 2010 - 2013. In conclusion: (1) the financial performance of PT. Bank BRI Syariah in the period 2010 - 2013 seen from CAR, NPL and ROA in the category of healthy, while ROA and LDR categorized as unhealthy; (2) the financial performance of PT. Bank Rakyat Indonesia Tbk in the period 2010 - 2013 seen from the CAR, NPL, ROA, BOPO, and LDR in the category of healthy; (3) The results of the comparison of different test financial performance. Bank Rakyat Indonesia Tbk and PT. Bank Rakyat Indonesia Syariah is concluded that for the CAR and ROA no significant difference, while the NPL ratio, ROA and LDR there is a significant difference, in which financial performance. Bank Rakyat Indonesia Tbk is better than the performance of spatial PT. Bank Rakyat Indonesia Syariah. Keywords: CAR, NPL, ROA, ROA, and LDR